The Relationship Between Self Control With Intensity of Playing Online Games on The School Children - Novita Febriyanti Rahayu Putri; Susanti Prasetyaningrum (Universitas Katolik Soegijapranata, 2018)
This research aims to know the relationship between self control with intensity of playing online games on the school children. The methods on this research is quantitative correlation, with the instrument is self control scale and intensity of playing online games scale. Quantity of subject is about 140 students of SDN Branta Paseser 1 Pamekasan who selected based on proportionate stratified random sampling techniques. The result shows that there is a relationship between self control with intensity of playing online games on the school children This means if the higher self control owned students, so the lower level intensity of playing online games. Beside that, the contribution of effective self control to the intensity of playing online games on the school children is about 64.6%.